REFORMULASI PENGATURAN TINDAK PIDANA PENCUCIAN UANG DENGAN MODUS CRYPTOCURRENCY DI INDONESIA - Muhammad Harifki; Davit Rahmadan; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Money laundering now covers many aspects and is developed in such a way and in linewith technological developments. Perpetrators of money laundering crimes use technologicaladvances as weapons and banking financial service providers as a place to store the proceedsof money laundering. One of them is the Cryptocurrency Mode which is currently widelycirculating in society. The development of Cryptocurrency has given rise to new methods inCryptocurrency as a new phenomenon in terms of payment transactions.This research is normative legal research. This is based on library research which takesquotations from reading books, or supporting books that are related to the problem to beresearched. This research uses secondary data sources consisting of primary, secondary andtertiary book materials. This research also uses qualitative data analysis and producesdescriptive data.From the results of the research and discussions carried out, several conclusions wereobtained, namely: First, the importance of additional regulations related to the criminal act ofmoney laundering using Cryptocurrency mode in Indonesia is considered important because itis currently widely used by Indonesian society. Second, the ideal regulation regarding thecriminal act of money laundering using the Cryptocurrency mode is to include elements of thelaw on money laundering. The author's suggestion is that there is a need to strengthen theauthority of law enforcement officials in eradicating criminal acts of money laundering usingCryptocurrency mode as well as giving more concrete attention to the formation of special lawsthat regulate Cryptocurrency as part of criminalization in Indonesia.Keywords: Reformulation, Money Laundering, and Cryptocurrency